2023
DOI: 10.1021/acsomega.2c05705
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of CO2-Based Polycarbonate Polyol with Highly Exfoliated Nanoclay

Abstract: Polypropylene carbonate (PPC) derived from carbon dioxide has been used as a precursor for the synthesis of polyurethane (PU). The high viscosity of the PPC is the key parameter hindering its processability during PU synthesis. Herein, a PPC nanocomposite with highly exfoliated nanoclay was prepared through a solution intercalation process. A wide range of nanoclay concentrations incorporated into the PPC were studied. The impacts of the nanoclay on the PPC were investigated in order to maintain the polymer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Therefore, the use of PPCD for the preparation of wet-type leather has economic and ecological benefits. 24,25 In the leather industry, in order to improve production efficiency, 24-h alkali resistance test is usually used to replace the traditional 7-day hygrothermal aging test at 85 C. It was found that WPL prepared by PPCD exhibited poor performance in alkali resistance test. When PPCD-based polyurethane was soaked in alkali solution, its mechanical properties decreased and its surface morphology changed, which limits the application of PPCD in leather industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of PPCD for the preparation of wet-type leather has economic and ecological benefits. 24,25 In the leather industry, in order to improve production efficiency, 24-h alkali resistance test is usually used to replace the traditional 7-day hygrothermal aging test at 85 C. It was found that WPL prepared by PPCD exhibited poor performance in alkali resistance test. When PPCD-based polyurethane was soaked in alkali solution, its mechanical properties decreased and its surface morphology changed, which limits the application of PPCD in leather industry.…”
Section: Introductionmentioning
confidence: 99%
“…From an economic point of view, using cheap CO 2 as raw material can reduce production costs by 10%–20%. Therefore, the use of PPCD for the preparation of wet‐type leather has economic and ecological benefits 24,25 …”
Section: Introductionmentioning
confidence: 99%